Physical exercise, social relationships, and bullying perpetration among school adolescents in China - Zhou, Hang; Chen, Ji‐Kang (Behavioral sciences & the law, 2024)
Despite contradictory empirical evidence, some suggest that physical exercise is directly related to bullying perpetration. Moreover, the quality of social relationships between adolescents and their parents, peers, and teachers has been proposed as a crucial mediator in the relationship between physical exercise and bullying perpetration. However, few empirical studies have examined such hypotheses. This study used data obtained from the 2014–2015 China Education Panel Survey to examine the direct association between physical exercise and bullying behaviors, as well as the indirect pathways from physical exercise to bullying that are mediated by teenagers' social relationship quality. The results showed no significant direct relationship between physical exercise and bullying behaviors. However, physical exercise has indirect associations with bullying behaviors mediated through social relationship quality, with peer relationships having the strongest mediating effect. The findings indicate that social relationships could mediate the association between physical exercise and bullying behaviors. The study suggests that future prevention and intervention programs should promote adolescents' participation in physical exercise and their social interactions with parents, peers, and teachers to reduce bullying perpetration.